2015
DOI: 10.1097/tp.0000000000000864
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Is Reversed in a Murine Model by Marginal Mass Syngeneic Islet Transplantation Using a Subcutaneous Cell Pouch Device

Abstract: BackgroundIslet transplantation is a successful β-cell replacement therapy for selected patients with type 1 diabetes mellitus. Although high rates of early insulin independence are achieved routinely, long-term function wanes over time. Intraportal transplantation is associated with procedural risks, requires multiple donors, and does not afford routine biopsy. Stem cell technologies may require potential for retrievability, and graft removal by hepatectomy is impractical. There is a clear clinical need for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 38 publications
0
89
0
Order By: Relevance
“…Unwanted 'off-target' mesodermal formation was reported with human ESCs in transplantation sites [Kroon et al 2008;Rezania et al 2012]. Many groups have tried selection of ESC-derived endocrine cells [Kelly et al 2015;Jiang and Morahan, 2015] or the use of micro-and macroencapsulation devices [Motte et al 2014;Agulnick et al 2015;Song and Roy, 2015] such as the Theracyte TM (Inc. manufactures, Laguna Hills, California) system to circumvent the undesired cell growth, but also to promote angiogenesis of the cells and to protect those from the host immune system [Pepper et al 2015]. PSC-derived functional insulin-producing cells were recently injected into a Theracytebased device (called Encaptra TM , San Diego, California) and subsequently transplanted subcutaneously [Agulnick et al 2015].…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…Unwanted 'off-target' mesodermal formation was reported with human ESCs in transplantation sites [Kroon et al 2008;Rezania et al 2012]. Many groups have tried selection of ESC-derived endocrine cells [Kelly et al 2015;Jiang and Morahan, 2015] or the use of micro-and macroencapsulation devices [Motte et al 2014;Agulnick et al 2015;Song and Roy, 2015] such as the Theracyte TM (Inc. manufactures, Laguna Hills, California) system to circumvent the undesired cell growth, but also to promote angiogenesis of the cells and to protect those from the host immune system [Pepper et al 2015]. PSC-derived functional insulin-producing cells were recently injected into a Theracytebased device (called Encaptra TM , San Diego, California) and subsequently transplanted subcutaneously [Agulnick et al 2015].…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…Recently, however, success in improving vascularisation for murine islet transplantation has been achieved within a macropolymer device implanted subcutaneously. 4 In this issue of Transplantation, Pepper et al 5 from the Edmonton group, extend their previous studies 6 showing evidence of creation of a vascularized subcutaneous space in mice using a novel "deviceless (DL) approach" to create a prevascularized site for islet implantation and transplanting a marginal mass of islets. Two-centimeter segments of a 5-French (Fr.)…”
mentioning
confidence: 86%
“…8,12,[14][15][16] It has been suggested that the lack of graft viability post-subcutaneous transplantation is due to the tissue's relatively low superficial tissue oxygen tension compared to other vascularized organs. 16 To thwart endogenous hypoxia and improve islet engraftment, subcutaneous engraftment strategies have employed growth factors, 17 scaffolds, 18-20 encapsulation polymers, 15,21 immunoisolating and non-immunoisolating devices, 11,[22][23][24][25][26] and oxygen delivery technologies. 17,24 While attractive due to the potential of avoiding systemic immunosuppression, a drawback of immunoisolating devices is the physical separation between host nutrient supply and the therapeutic cells within the device.…”
Section: Discussionmentioning
confidence: 99%